The guarachas of “El Guayabero”: a poetic chronicle of contemporary Cuba (Revista de Crítica Literaria Latinoamericana, 2013)
Similar to other manifestations of oral tradition in American culture, the guaracha has not received its deserved attention from critics, despite being an incredibly prominent genre of popular production in Cuba and the Caribbean. It is this lack of attention that this article intends to remedy. Rooted in the intersection of Indigenous, Hispanic, and African cultures and bound to the proverbial Cuban banter, the guaracha has journeyed from its beginnings in the bufo theatre to its current merging with other lyrical-musical forms, demonstrating its versatility and ability to adapt with the times. Through analyses of lyrics by Faustino Oramas - also known as "The guayabero" - who reached noteworthy popularity throughout Cuba at the end of the 20th century, the poetic characteristics of the genre shine through.
Keywords: guaracha; Faustino Oramas; Cuban popular music; "bufo" theater